Kekuatan dan Kelemahan Tafsir Al-Qur’an bi Al-Sunnah - Ahmad Khoirul Fata (Farabi, 2017)
Tafsir al-Qur'an bi al-Sunnah as part of tafsir bi al-ma'thur has an important position in the process of understanding the meanings of the Qur'an. Despite the differences in defining the meaning of the Sunnah or Hadith, the Muslim scholars (Ulama) placed this interpretations as the most authoritative interpretation among other interpretation models. There are two forms of the Qur'an bi al-Sunnah tafsir as described Abdullah Saeed: verbatim (direct) and fi'li (deeds, indirect). However, as a form of tradition-based interpretation, such interpretation is considered less has shortcomings in its limitations in reaching many contemporary problems. That's because not all the verses of the Koran described directly by the Prophet Muhammad. Herein lies the urgency of developing ijtihad so that the verses of the Koran that can still be understood better by staying pivot on the explanation of the Prophet Muhammad or the verses of the Koran more.